Some peculiarities of the development of modern philosophy - TURSUNOVNA, SHARIPOVA OYGUL; BURHANOVNA, HAYDAROVA HANIFA; FAYZULLAYEVICH, DJURAYEV SHODMON; MUNISXON, GULAMOVA (The journal of contemporary issues in business and government, 2021)
The article is devoted to some of the features of the development of philosophy in the modern world. Features of the development of philosophy in the modern world has many directions. Each of them has a specific character. The main aspects of the development of modern philosophy are given on the basis of some elements of the evolution of this subject. The features of the development of modern philosophy are relevant and they require separate scientific research.